Anti-quorum sensing and antibacterial activities of Satureja sahendica hydroalcoholic extract against avian isolate of Salmonella Typhimurium - Razieh Sharchi; Jalal Shayegh; Somayyeh Hosseinzadeh (The Iranian Journal of Veterinary Science and Technology, 2020)
Quorum sensing (QS) is a cell density dependent mechanism used by many pathogenic bacteria for regulating virulence gene expression. Inhibition or interruption of QS by herbal remedies has been suggested as a new strategy for fighting against antibiotic resistant bacteria. The aim of this study was to evaluate the antibacterial activity of Satureja sahendica hydroalcoholic extract (SSHE) against Salmonella Typhimurium (S. Typhimurium) isolates, and to assess the impact of sub-inhibitory concentrations of this extract on the QS-associated gene (sdiA) expression. Using the Soxhlet method, hydroalcoholic extract of S. sahendica leaves was prepared and antimicrobial effects of the SSHE were determined by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methodS. The reverse transcription quantitative PCR (RT-qPCR) assay was used to analyze the expression of sdiA in 20 S. Typhimurium isolates from poultry flocks in response to the treatment of sub-inhibitory concentrations of SSHE at 60-min time point. The MIC values of SSHE against S. Typhimurium isolates were ranged from 0.29-4.68 mg/ml-1 and MBC values were ranging from 75-150 mg/ml-1. The results also indicated that the expression of sdiA gene was reduced in S. Typhimurium isolates triggered by the treatment of SSHE comparatively with those from the control cultureS. Findings suggest that SSHE possess the antibacterial and anti-QS activity and can be used to control the expression of virulence genes in pathogenic bacteria, such as S. Typhimurium.